Housing decision making technical information: an approach for improving quality housing delivery during the initiation development phase process - Zainal, Rozlin; Mohamed, Sulzakimin; Sarpin, Norliana; Seow, Ta Wee; Shamsudin, Zarina; Mat Radzuan, Indera Syahrul (ExcelingTech Pub, 2018)
Incomplete communication between decision maker, proposer and secretariat happened due to time constraint and distance's factor among them in decision making process for housing development project. Consequently convenience to information becomes limited due to the restricted amount of data given by developer. The problem is to make the best decision in construction; it must come from various information sources and specialists, especially in housing where the sector is near to the public (social) objective. Due to these decision making problems, developer faces a late delivery and sick housing project conflict. This paper aims to identify the technical decision making information for housing development at the initiation phase in Malaysia. Delphi method is employed by using questionnaire survey which involved 50 private developers for the first round of data collection. However, only 34 developers contributed to the second round of the data collection process. At the last round, only 12 developers were finalised as the main contributor in the final process. As a result, the findings are work schedule, location and size of project are most necessary information in technical information part which are required during decision making for housing development among Malaysian developers. Moreover, the advancement of skill must be improved and developers should not be easily pleased with their achievement as the information technology advances at a pace we can hardly keep up with.